Decline in firing technology or poorer fuel resources? High-temperature thermoluminescence (HTTL) archaeothermometry of Neolithic ceramics from Pool, Sanday, Orkney - Spencer, Joel Q. G.; Sanderson, David C. W. (My University, 2012)
The Neolithic ceramic assemblage from the multi-period coastal settlement at Pool on the island of Sanday, Orkney is unique because it stratigraphically spans both the earlier round-based (including possible Unstan bowls) and later flat-based (‘Grooved Ware’) traditions. High-temperature thermoluminescence (HTTL) analysis objectively demonstrates that ceramics from the earliest Neolithic layers have been consistently better fired compared to examples from later layers. We suggest two interpretations of these data: either firing technology declined with changing social structures and/or adoption of a different ceramic tradition or that there was greater pressure on fuel resource and management in the later Neolithic. Paleoenvironmental and chronological evidence indicate climatic deterioration in the later Neolithic, which adds further support to an interpretation of a poorer fuel resource at that time. In addition to studies of the HTTL signal, analysis of the ambient temperature modification of the TL signal has potential to support or evaluate dating evidence, and is readily applicable to optically stimulated luminescence (OSL) age data.
Keywords: Orkney Neolithic; Ceramics; High-temperature thermoluminescence; Thermal exposure; Firing technology; Fuel resources; Palaeoclimate